Design and evaluation of a novel biodegradable inferior vena cava filter. (March 2019) - Yang, Caihong; Ma, Fengcang; Gao, Chenguang; Kang, Yahong; Zhang, Guoyi; Liu, Ping; Jiang, Hongyan; Chang, Zhaohua
Inferior vena cava filter has been increasingly applied in clinical practice to prevent pulmonary embolism. Nowadays, various complications after implanting conventional filters seriously hinder clinical applications. Therefore, in this paper, a novel biodegradable inferior vena cava filter was designed based on biodegradable materials, which is an hourglass-like filter anchored inside a stent structure fixed by connecting fibers. Firstly, mechanical tests in crimp were performed to study the expansion properties of the filter, showing that the biodegradable inferior vena cava filter could achieve self-expansion easily. Furthermore, the biodegradable inferior vena cava filters and fibers were incubated in phosphate buffer media (pH = 7.4 ± 0.2) at 37°C for six months. Scanning electron microscope micrograph showed that the stents exhibited no significant dimensional and structural changes and had enough radial force to support the vessel. During the degradation period, the results of scanning electron microscope, gel permeation chromatography, differential scanning calorimetry and tensile strength analysis confirmed that the degradation rate of the hourglass-like filter was faster than the connecting fibers, achieving progressive degradation and thus avoiding the polymer fragments from blocking vessel. Cytotoxicity and hemolysis assay demonstrated good biocompatibility of the filter. For 5 mm × 10 mm sized thrombus, in vitro simulated thrombus capture test showed that the mean trapping efficiency of the filter was 90%, which was comparable to traditional inferior vena cava filter. In conclusion, all results exhibited that the as-designed biodegradable inferior vena cava filter has a potential in clinical application for patients who are at temporary high risk of venous thromboembolism.